The Design of Portable Battery Charging Devices Using Motorcycle Wheel Round - Jalil, Feranita; Firdaus; Safrianti, Ery; Hidayat, Ade (Electrical Engineering Department, Faculty of Engineering, Universitas Riau, 2019)
The design of the utilization of motorcycle wheel rotation for portable battery charging aims to make a device that can be used to charge batteries or gadgets by utilizing motorcycle wheel rotation. This tool works by using the rotation of a motorcycle's wheels into electric power for charging power bank or cell phone needs. This tool consists of 3 parts, namely dynamo, a rectifier circuit, and a regulator circuit. From testing the tools that have been made, it is proven that the device can work and produce an output voltage of 5V and a maximum current of 0.95A. The power produced is 4.75 Watt. This tool can charge a cell phone for 0-100% in 226 Minutes and charge a power bank for 50% for 131 Minutes. The recommended speed of the motorbike when charging is 30Km / h.